FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM (STUDI KASUS PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2018-2020) - A. Ririn Kurniawan; Budi Astuti (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to examine the influence of capital structure, company size, ROA, and leverage on share prices in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The sample in this research consisted of 13 various industrial companies listed on the BEI (Indonesian Stock Exchange) during 2018-2020 which were selected based on certain criteria using purposive sampling. With an observation period of 3 years, the research sample consisted of 39 samples. The analytical method used is multiple linear regression analysis and the coefficient of determination is processed using the SPSS program. The results of multiple linear regression tests prove that capital structure has no effect on stock prices, company size has an effect on stock prices, ROA has no effect on stock prices, and leverage has no effect on stock prices. The results of the coefficient of determination test (Adjusted R²) show that 30.4% of the variation in stock returns can be explained by independent variables, while the remaining 69.6% is explained by other variables not in this study. Keywords: Share Price, Capital Structure, Company Size, Return On Assets, Leverage